A geometric description of the Atiyah-Hirzebruch spectral sequence for B-bordism - Tene, Haggai (Münster journal of mathematics, 2017)
In this paper we give a geometric description of the general term and the differential of the Atiyah–Hirzebruch spectral sequence for B-bordism. This description is given in terms of bordism classes of maps from stratifolds. We illustrate that with a computational example. We also discuss the case of a general homology theory, where this description is given in terms of the Postnikov sections of the given theory.
Gesehen am 12.04.2018